A novel topology for single-inductor single input triple output DC-DC power converter - Edara Sreelatha; Alagappan Pandian; Mohana Sundaram Kuppusamy (Institute of Advanced Engineering and Science, 2023)
A single input triple output (SITO) DC-DC power converter circuit derived from a single inductor boost converter is proposed in this paper. Like multi-level inverters, many electronic circuit applications need multiple DC output voltages. Using different power supply circuits increases the system cost, size, and weight. The multiple-input, multiple-output power conversion system integrates multiple sources and outputs and uses a single controller. The integrated operation results in simple structure, low cost, and size, making it suitable for different power conversions, including renewable sources. In this series, the proposed single-inductor single-input triple-output (SI-SITO) DC-DC power converter is designed to produce three independent DC output voltages and two dependent output voltages. The proposed circuit is derived from a conventional boost converter made up of a single inductor. The advantage of this proposed circuit is the use of minimum components and simple control strategies. The design and performance analysis is done using Mat Lab simulation. The experimental results show the benefits of the proposed circuit.